Online quality assurance system in vocational schools using the website: A user satisfaction perspective - S. Hadi; W. M. Wijaya; R. Utari; W. Wijayanti; C. S.A. Jabar (Russian State Vocational Pedagogical University, 2023)
Introduction. This study was conducted to identify the factors that influence user satisfaction to determine the quality of the website (online system) for quality assurance in vocational education from the user's point of view and to provide the best recommendations for improving the quality of the vocational school quality assurance online system.Aim. This study aims to analyse the quality of the vocational school quality assurance website that affects user satisfaction using the WebQual model.Methodology and research methods. This research used structural equation modelling - partial least square (PLS-SEM) analysis. The purposive sampling technique was chosen to determine the sample of respondents from operators or users of the quality assurance website from 36 vocational schools in Yogyakarta Province, Indonesia.Results. Based on the analysis results, it was found that the service interaction quality factor significantly influenced the e-service quality of the vocational school website for quality assurance, which then directly affected website user satisfaction.Practical significance. This research has implications for developing vocational school website for quality assurance to optimise the website function. This research also has implications for schools to facilitate performance reporting through quality assurance website.